MEMAHAMI PENGERTIAN, MACAM-MACAM, UNGKAPAN-UNGKAPAN DAN URGENSI ASBAB AN -NUZUL - Indina Sa’adah; Nur Anisa; Selvy Puspita Anggraeni; Umar Al-Faruq (Pondok Pesantren Baitul Qur`an Sambas, 2024)
There are several scholars who have different opinions in defining asbab an-Nuzul, including Az-Zarqani, Ash-Shabuni, Shubhi Shaleh and Manna' Al-Qattan. However, all of them concluded that asbab an-nuzul was the incident or event that was the background for the revelation of the verses of the Qur'an, in order to answer, explain and resolve the problems that arose from this incident. Asbab an-nuzul is historical material that can be used to provide information on the revelation of a verse of the Qur'an and provide context in understanding its commands. Of course, these materials only cover events at the time when the Koran was still revealed. In terms of the number of causes and verses revealed, asbab an-nuzul is divided into two, namely the first, Ta'addud Al-Asbab Wa Al-Nazil Wahid (the reason behind the revelation of one verse) and the second, Ta'adud an-nazil wa al-asbab wahid (the reasons behind the revelation of several verses). The expressions or editorials used by friends to show the revelation of the Koran are not always the same. The editorials are broadly grouped into two categories, namely Sarih (clear) and Muhtamilah (still possible or uncertain). Asbab an-nuzul has a very important meaning in interpreting the Koran. A person will not achieve good understanding if he does not understand the history of a verse's asbab an-nuzul. Understanding asbab an nuzul will be very helpful in understanding the context of the revelation of the verse. It is very important to apply the verses to different cases and occasions. The opportunity for mistakes to occur will definitely be greater if you ignore the history of asbab an-nuzul.